Cursos Curtos Online Síncronos para Meninas do Ensino Médio e Concluintes e para Professoras do Ensino Básico - Pimentel, Maria da Graça C.; Eusébio, Juliana; Goularte, Rudinei; Leite, Uthant V.; Picoli, Helen S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e Web, 2024)
Globally, women are underrepresented among students and professionals in Information Technology. In Brazil, high school girls have limited knowledge about Computing and face gender stereotypes, perceiving the field as male-dominated with low female representation. Our project offers short, free, synchronous online courses in Introduction to Computing with Python for high school girls and graduates, and introductory computational thinking courses with Scratch for elementary school teachers. Since October 2021 , 1249 high school girls from across Brazil have completed one of the courses for girls in the 27 classes offered up to June 2024. Since February 2023, 119 elementary school teachers have completed one of the courses for teachers. This report presents the evolution of our courses, details their approach, reports quantitative results, includes testimonials from graduates, and tracks the progress of those who have reported pursuing higher education in the field.